Interseeding timing of cowpea (Vigna unguiculata L. Walp.) living mulch on weed diversity, physical soil properties and performance of maize (Zea mays L.) - Berdjour, A. (University of Development Studies, 2019)
This trial was conducted to determine cowpea living mulch and maize maturity type effect on soil physical properties, maize yield and weed management. The study was a 3 x 4 factorial experiment laid out in Randomised Complete Block Design with 3 replications. Three maize maturity types: extra early Abontem, early Omankwa and medium Obatanpa and four living mulch systems: cowpea living mulch interseeded same day with maize (SDWM), cowpea living mulch interseeded 1 Week after planting maize (WAPM), cowpea living mulch interseeded 2 WAPM and sole maize (control) were used as treatments. The maize was planted at a spacing of 75 x 40 cm and interseeded with cowpea living mulch planted in between maize rows at an intra-spacing of 20 cm, resulting in a 1:1 row arrangement. Data was collected on soil physical properties, maize growth, yield and yield components, weed biomass and diversity. Planting cowpea as mulch in maize reduced (p < 0.05) soil temperature and increased (p < 0.05) soil moisture content than the control at vegetative, tasselling and harvest growth stage of the maize. Maize plant height at harvest, leaf area index of maize at 6 WAPM and days to 50% tasselling were significantly affected by cowpea living mulch and maize maturity type interaction. Cowpea living mulch significantly increased maize grain yield, with cowpea living mulch at 1 WAPM recording the highest grain yield of 2285.9 kg/ha. Cowpea living mulch significantly reduced weed biomass at 6, 9 and 12 WAP. Maize maturity type affected (p < 0.05) parameters such as plant height, leaf area index, 50% tasselling and silking, stover yield and harvest index. Cowpea interseeded SDWM and 1 WAPM best improved soil physical properties, maize yield and reduced weed diversity and biomass. Therefore, for enhanced maize yield and optimum weed control, farmers with enough labour can inter-seed maize with cowpea live mulch on the same day (SDWM). Alternatively, those face with labour scarcity could adopt maize with cowpea interseeded at 1 WAPM.